2019
DOI: 10.1007/s11682-019-00093-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute pediatric traumatic brain injury severity predicts long-term verbal memory performance through suppression by white matter integrity on diffusion tensor imaging

Abstract: Mediation analysis was used to investigate the role of white matter integrity in the relationship between injury severity and verbal memory performance in participants with chronic pediatric traumatic brain injury (TBI). DTI tractography was used to measure fractional anisotropy (FA) within the corpus callosum, fornix, cingulum bundles, perforant pathways, and uncinate fasciculi. Injury severity was indexed using Glasgow Coma Scale (GCS) scores obtained at the time of the injury. Verbal memory was measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Specifically, our findings revealed that the TBI group had significantly lower FD, FC and FDC in several WM tracts, including the commissural tracts (corpus callosum, fornix), association fibres (e.g., superior longitudinal fasciculus), and projection fibres (e.g., internal capsule, medial lemniscus, superior corona radiata, external capsule). These results are in line with previous diffusion MRI studies of pediatric TBI (including work from our group), utilising metrics derived from DTI (for recent reviews, see Lindsey et al, 2019 , Wallace et al, 2018b , Wallace et al, 2018a , Zamani et al, 2020 ). However, previous studies have demonstrated that FBA can offer more specific, directly interpretable, and within-voxel white matter metrics, which contrasts with other widespread diffusion imaging frameworks, like DTI, that are less specific and cannot exploit sub-voxel level information (for example, DTI cannot resolve crossing fibres and hence not all white matter voxels can be accurately modelled within the voxel-based analysis framework; see Jeurissen et al, 2013 ; Mito et al, 2018 , Raffelt et al, 2015 ).…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, our findings revealed that the TBI group had significantly lower FD, FC and FDC in several WM tracts, including the commissural tracts (corpus callosum, fornix), association fibres (e.g., superior longitudinal fasciculus), and projection fibres (e.g., internal capsule, medial lemniscus, superior corona radiata, external capsule). These results are in line with previous diffusion MRI studies of pediatric TBI (including work from our group), utilising metrics derived from DTI (for recent reviews, see Lindsey et al, 2019 , Wallace et al, 2018b , Wallace et al, 2018a , Zamani et al, 2020 ). However, previous studies have demonstrated that FBA can offer more specific, directly interpretable, and within-voxel white matter metrics, which contrasts with other widespread diffusion imaging frameworks, like DTI, that are less specific and cannot exploit sub-voxel level information (for example, DTI cannot resolve crossing fibres and hence not all white matter voxels can be accurately modelled within the voxel-based analysis framework; see Jeurissen et al, 2013 ; Mito et al, 2018 , Raffelt et al, 2015 ).…”
Section: Discussionsupporting
confidence: 89%
“…For this reason, early brain insult likely affects the maturation of the frontal and temporal cortices, as well as the white matter pathways connecting them to other areas of the brain. Such disruption is known to have detrimental and long-term consequences on the development of critical neurobehavioral functions localized within these regions, such as executive function (10,11), learning and memory (12), emotional control (13), behavioral self-regulation (14), and social adaptive behavior (15).…”
Section: Introductionmentioning
confidence: 99%
“…Following DAI, as the loss of white matter integrity causes neural network connectivity disruptions, acute and long-term neurobehavioral outcomes can be negatively affected (35,36). However, functional outcome after DAI is difficult to predict as some children have profound disability while others make a better recovery (37)(38)(39)(40)(41)(42). A multitude of sophisticated neuroimaging studies have been performed to correlate pediatric DAI and outcome (41,(43)(44)(45)(46)(47).…”
Section: Introductionmentioning
confidence: 99%